Investment in Green Energy and other projects in Gujarat - Reliance Industries Limited (2022)
Reliance is investing Rs 5.95 lakh crore in Green Energy and other projects in Gujarat over a span of 10 to 15 years. The investment will help in setting up a 100 GW Renewable Energy Power Plant and develop a Green Hydrogen ecosystem. RIL will also develop an ecosystem for assisting Small and Medium Enterprises (SMEs) and encourage entrepreneurs to embrace new technologies and innovations leading to captive use of Renewable Energy and Green Hydrogen.